Dissemination of Disaster Communication and Information via Instagram @bpbdkaro - Lestari, Puji; Paripurno, Eko Teguh; Subekti, Hikmat; Barus, Catrinadia Christie Br.; Isyana, Elisabeth (RSF Conference Series: Business, Management and Social Sciences, 2021)
The social media Instagram @bpbdkaro as a source of communication and disaster information dissemination in the Karo community is no longer active. The purpose of this study was to find a disaster communication planning model in the communication and information dissemination process from the Karo Regency Regional Disaster Management Agency (BPBD) to the community through the Instagram @bpbdkaro social media account. This study uses qualitative evaluation research methods, data collection techniques with Focus Group Discussion and interviews with Instagram managers, the Head of Planning for the Regional Disaster Management Agency (BPBD), and field observations. Quantitative evaluation method with data collection techniques is carried out online through Google Form to 50 people who use social media randomly. The evaluation results show that Instagram social media is used by the majority of respondents (28%) as the main source of searching for disaster information in Karo, but @bpbdkaro social media is not active because the Karo Regency BPBD does not dare to face negative comments from the community and the unavailability of human resources to manage it. This causes the dissemination process of disaster communication and information through social media Instagram @bpbdkaro not going well to achieve the goal due to the lack of elements of communication planning. The results of the evaluation of researchers with BPBD Karo Regency have carried out communication planning referring to the Cutlip and Center planning theory by covering elements of fact determination, planning, communication, and evaluation. The theoretical new findings in this study provide additional elements of communication competence and resources in the Cutlip and Center Communication Planning Model. The substance of this research contributes in the form of recommendations for communication planning models for the dissemination of disaster communication and information through social media.